Anti-cholesterol Activity of Kemuning Leaf Extract (Murraya paniculata (L.) Jack.) Using Different Extraction Methods and Solvents - Ardhalya Octarizha; Devy Susanty; Ade Ayu Oksari; Nurlela Nurlela (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2025)
High cholesterol levels may accumulate in blood vessels, causing blockages. Reducing cholesterol levels using biological materials is an essential area of research currently to minimize the impact of chemical drugs. One of the biological materials with potential as an anti-cholesterol is the Kemuning plant (Murraya paniculata (L.) Jack). This study aims to determine the content of secondary metabolites, total phenolic content, total flavonoid content, and anti-cholesterol activity of Kemuning leaf extract, with variations in extraction methods and solvents. The extraction methods used were ultrasound-assisted extraction (UAE) and maceration. The solvents used in this study had different polarities, namely 96% ethanol, ethyl acetate, and n-hexane. The extract obtained from variations in extraction methods and solvents was tested for phytochemistry, total phenolics, total flavonoids, and in vitro anti-cholesterol activity using the Liebermann-Burchard method. The results showed that Kemuning leaf extract contained secondary metabolite compounds with anti-cholesterol activity. The best extraction method for secondary metabolites was the UAE method using 96% ethanol; however, the best EC50 value was obtained from maceration with ethyl acetate. The total phenolic content of the 96% ethanol extract of Kemuning leaf using the UAE method was 61.48 mg Gallic Acid Equivalent (GAE/g extract), the total flavonoid content was 100.77 mg Quercetin Equivalent (QE/g extract), and the anti-cholesterol activity had an EC₅₀ of 13.03 µg/mL.